Value Creation-Based Financial Performance, Factors Macroeconomics and its Influence on Stock Returns Agricultural Sector - Sujatmiko Sujatmiko; Moh Hatta; Nurdwiana Sari Saudi; Al Kausar Al Kausar; Muh Ashary Anshar (Postgraduate, University of Mataram, 2023)
The primary performance metric used by investors to evaluate the efficiency of capital investments is stock return. After the mining industry, the agricultural sector's stock price index volatility from 2015 to 2021 produced the second-lowest annualized return. Businesses can generate corporate value that is closely tied to stock returns by utilizing value creation-based performance analysis (EVA, MVA, Q-Tobin). Furthermore, stock returns may also be impacted by outside variables. The objectives of this study are to: (1) examine the financial performance of agricultural companies using Q-Tobin, MVA, and EVA; (2) examine the relationship between Q-Tobin, MVA, and EVA and macroeconomic factors (exchange rates and inflation) on stock returns in the agricultural sector; and (3) draw managerial conclusions from the analysis's findings. Eight companies in the agricultural sector that were listed on the Indonesia Stock Exchange prior to 2015 provided the data. In order to ascertain the impact of macroeconomic variables, EVA, MVA, Q-Tobi, and panel data on stock returns, this study used descriptive analysis to evaluate the EVA, MVA, and Q-Tobi of each firm. The majority of the enterprises had negative EVAs, according to the results. However, the MVA study reveals that most businesses achieve positive MVA. The majority of the companies produce a value of q<1, according to the Q-Tobin data. Only the MVARET and Q-Tobin RET variables significantly improve stock returns, according to the REM analysis. Exchange rates, inflation, EVARET, and fictitious crises don't significantly affect stock returns.